"They Understand What You're Going Through": Experientially Similar Others, Anticipatory Stress, and Depressive Symptoms. (March 2021) - Grace, Matthew K.
Past research demonstrates that experientially similar others—people who have confronted the same stressor or who occupy the same social role—are uniquely equipped to provide empathic understanding and tailored coping strategies to individuals navigating comparable, taxing circumstances. Using the case of premedical education, fixed-effects regression analyses of egocentric network data (N = 286) indicate that premeds whose support networks include a greater proportion of premedical peers over time experience fewer depressive symptoms. However, among premeds who report greater anticipatory stress about failing to achieve medical school admission, the presence of additional peers in support networks strengthens the detrimental effects of anticipatory stress. Qualitative data (n = 39) shed light on this empirical puzzle. Although peers offer a broad spectrum of support functions, they can also accentuate stressors or serve as a basis for negative social comparison. These findings introduce new considerations for theorizing the role of similar other support in the stress process.